2014
DOI: 10.1080/10934529.2014.865454
|View full text |Cite
|
Sign up to set email alerts
|

Different susceptibilities of bacterial community to silver nanoparticles in wastewater treatment systems

Abstract: The release of silver (Ag) nanoparticles (NPs) into sewage streams has heightened concerns about potential adverse impacts on wastewater treatment processes. Here, we show that the rate constants of both biological nitrification and organic oxidation decreased exponentially with an increase in the Ag NP concentration, but nitrification was more severely inhibited than the organic oxidation even at low Ag NP concentrations (<1 mg Ag L(-1)) in batch experiments. The long-term exposure effects of Ag NPs on activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Beside of nCeO 2 , other engineered metal oxides-NPs such as nAg NPs (Das et al 2012), nZnO NPS (Meli et al 2016) and TiO2 NPs (Shah et al 2014) have also been reported to have toxic effects on microbial community from several ecosystem. Jeong et al (2014) also revealed the impact of nAg-NPs on bacterial community from wastewater treatment systems. These authors revealed that nitrifying bacteria are most susceptible to NPs such as nAg.…”
Section: Discussionmentioning
confidence: 99%
“…Beside of nCeO 2 , other engineered metal oxides-NPs such as nAg NPs (Das et al 2012), nZnO NPS (Meli et al 2016) and TiO2 NPs (Shah et al 2014) have also been reported to have toxic effects on microbial community from several ecosystem. Jeong et al (2014) also revealed the impact of nAg-NPs on bacterial community from wastewater treatment systems. These authors revealed that nitrifying bacteria are most susceptible to NPs such as nAg.…”
Section: Discussionmentioning
confidence: 99%
“…At sublethal concentrations, Ag-NPs can upregulate amoA ( Yang et al, 2013 ). A few reports have documented the adverse effects of Ag-NPs on nutrient removal from wastewater are dose dependent and nutrient removal can recover with time ( Chen et al, 2013 ; Alito and Gunsch, 2014 ; Jeong et al, 2014 ). The effects of Ag-NPs on other microbial functional groups in biological wastewater treatment systems are far less well studied.…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs are believed to interfere with essential bacterial cell functions upon contact 6 , although the exact mechanism of the antimicrobial effect is still subject to debate 7 . However, after their intended use, the waste nanoparticles are hard to recover or deactivate in solid-waste incineration plants 8 or wastewater treatment systems 9 . Over time, processes such as sulphidation may convert the AgNPs to a less hazardous form 10 , but the long exposure of their core in the environment 11,12 and prolonged activity after their intended application 13 may adversely affect many ecosystems 14,15 .…”
mentioning
confidence: 99%